Engineering Nanocomposites For Precision Medicine And Therapeutic Applications-A Review - Khalid, Mohammed; Kumar BS, Ashok; NS, Disha; P M, Hema (Journal of Neonatal Surgery, 2025)
Nanocomposites, based on the inclusion of two or more phases in which at least one phase is nanoscale, have drawn immense interest due to their emergent properties based on synergistic interactions between their constituents. These materials have great value particularly in biomedicine. Nanocomposites represent a strong contender in drug delivery, dermatology, oral care, cancer therapy, vaccines, gene therapy, and enhancing blood circulation. The paper aims at comprehensively reviewing the current state of nanocomposite applications in biological fields, especially relating to their application in therapy and the challenges that accompany them. Nanocomposites have many unique advantages, such as controlled drug release, better biocompatibility, and enhanced efficacy in targeted delivery. All these features make them highly effective in medical treatments across various biological applications. Nonetheless, the current review's findings do emphasize that while these materials are promising, there is still a way to go in terms of safety assessment, precision of drug release, targeted delivery, and biocompatibility. Additionally, challenges arise from the scalability and reproducibility of the processes, environmental impact studies, standardization, and issues at the regulatory level all contribute to additional barriers for widespread implementation. Scaling up in production, reduction of environmental impacts, and developing comprehensive regulatory frameworks will be important to completely enhance the potential of nanocomposites within biomedical applications. Research and studies in these areas should thus be targeted to ensure an optimization of their use and to surpass the present barriers in the field.